Energy-energy correlation in hadronic Higgs decays: analytic results and phenomenology at NLO - Gao, Jun; Shtabovenko, Vladyslav; Yang, Tong-Zhi (The journal of high energy physics, 2021)
A bstract In this work we complete the investigation of the recently introduced energy-energy correlation (EEC) function in hadronic Higgs decays at next-to-leading order (NLO) in fixed-order perturbation theory in the limit of vanishing light quark masses. The full analytic NLO result for the previously unknown EEC in the H → q q ¯ + X channel is given in terms of classical polylogarithms and cross-checked against a numerical calculation. In addition to that, we discuss further corrections to predictions of the Higgs EEC event shape variable, including quark mass corrections, effects of parton shower and hadronization. We also estimate the statistical error on the measurements of the Higgs EEC at future Higgs factories and compare with the current perturbative uncertainty.